Crossing Academic Boundaries for Diagnostic Safety: 10 Complex Challenges and Potential Solutions From Clinical Perspectives and High-Reliability Organizing Principles. (February 2022) - Yousef, Elham A.; Sutcliffe, Kathleen M.; McDonald, Kathryn M.; Newman-Toker, David E.
Objective: We apply the high-reliability organization (HRO) paradigm to the diagnostic process, outlining challenges to enacting HRO principles in diagnosis and offering solutions for how diagnostic process stakeholders can overcome these barriers. Background: Evidence shows that healthcare is starting to organize for higher reliability by employing various principles and practices of HRO. These hold promise for enhancing safer care, but there has been little consideration of the challenges that clinicians and healthcare systems face while enacting HRO principles in the diagnostic process. To effectively deploy the HRO perspective, these barriers must be seriously considered. Method: We review key principles of the HRO paradigm, the diagnostic errors and harms that potentially can be prevented by its enactment, the challenges that clinicians and healthcare systems face in executing various principles and practices, and possible solutions that clinicians and organizational leaders can take to overcome these challenges and barriers. Results: Our analyses reveal multiple challenges including the inherent diagnostic uncertainty; the lack of diagnosis-focused performance feedback; the fact that diagnosis is often a solo, rather than team, activity; the tendency to simplify the diagnostic process; and professional and institutional status hierarchies. But these challenges are not insurmountable—there are strategies and solutions available to overcome them. Conclusion: The HRO lens offers some important ideas for how the safety of the diagnostic process can be improved. Application: The ideas proposed here can be enacted by both individual clinicians and healthcare leaders; both are necessary for making systematic progress in enhancing diagnostic performance.